Applications of Herbal Medicine to Treat Autosomal Dominant Polycystic Kidney Disease - Shao, Guangying; Zhu, Shuai; Yang, Baoxue (Frontiers in Pharmacology, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary kidney disease, which is featured by progressively enlarged bilateral fluid-filled cysts. Enlarging cysts destroy the structure of nephrons, ultimately resulting in the loss of renal function. Eventually, ADPKD develops into end-stage renal disease (ESRD). Currently, there is no effective drug therapy that can be safely used clinically. Patients progressed into ESRD usually require hemodialysis and kidney transplant, which is a heavy burden on both patients and society. Therefore, looking for effective therapeutic drugs is important for treating ADPKD. In previous studies, herbal medicines showed their great effects in multiple diseases, such as cancer, diabetes and mental disorders, which also might play a role in ADPKD treatment. Currently, several studies have reported that the compounds from herbal medicines, such as triptolide, curcumin, ginkolide B, steviol, G. lucidum triterpenoids, Celastrol, saikosaponin-d, Sparganum stoloniferum Buch.-Ham and Cordyceps sinensis, contribute to the inhibition of the development of renal cysts and the progression of ADPKD, which function by similar or different mechanisms. These studies suggest that herbal medicines could be a promising type of drugs and can provide new inspiration for clinical therapeutic strategy for ADPKD. This review summarizes the pharmacological effects of the herbal medicines on ADPKD progression and their underlying mechanisms in both in vivo and in vitro ADPKD models.